Domain‐based local pair natural orbital methods within the correlation consistent composite approach. Issue 8 (31st December 2019) - Patel, Prajay; Wilson, Angela K.
Abstract : Ab initio composite approaches have been utilized to model and predict main group thermochemistry within 1 kcal mol −1, on average, from well‐established reliable experiments, primarily for molecules with less than 30 atoms. For molecules of increasing size and complexity, such as biomolecular complexes, composite methodologies have been limited in their application. Therefore, the domain‐based local pair natural orbital (DLPNO) methods have been implemented within the correlation consistent composite approach (ccCA) framework, namely DLPNO‐ccCA, to reduce the computational cost (disk space, CPU (central processing unit) time, memory) and predict energetic properties such as enthalpies of formation, noncovalent interactions, and conformation energies for organic biomolecular complexes including one of the largest molecules examined via composite strategies, within 1 kcal mol −1, after calibration with 119 molecules and a set of linear alkanes. © 2019 Wiley Periodicals, Inc. Abstract : To expand the size limitations of composite methodologies, the correlation consistent Composite Approach (ccCA) was combined with the domain‐based local pair natural orbital (DLPNO) methods. Denoted as DLPNO‐ccCA, this method targets main group thermochemistry and achieves chemical accuracy (1 kcal/mol) with an 87% CPU time reduction compared to ccCA. DLPNO‐ccCA was applied to molecules of increasing size and complexity including biomolecular complexes and one of the largest molecules examined via composite strategies after calibration.